Pengaruh Usia dan Masa Kerja terhadap Produksi Tenaga Kerja di PT. Galva Kami Industry Cikarang - Jamaludin, Agus; Widiarto, Toto; Sutina, Sutina; Jumaeroh, Siti (Sosio e-Kons, 2024)
This research aims to determine the effect of age and length of service on workforce productivity at PT. Our Galva Industry Cikarang. The total sample was 72 people using research methods: Field research method, namely a field study method using direct observation at the research location and distributing questionnaires to employees, also using the library research method, namely a library study method by reading books, journals, theses and websites, The nature of the research data is qualitative data, the research instrument used is distributing questionnaires, the data processing technique uses SPSS version 26. The data analysis technique is: Classical Test which includes the Normality Test, Multicollinearity Test, and Heteroscedasticity Test, while the Statistical Test is the Test: Multiple Linear, Multiple Correlation Test, Coefficient of Determination Test, Hypothesis Test and F Test. Based on the results of hypothesis testing, it shows that the variables age (X1) and length of service (X2) simultaneously influence labor productivity (Y). The results of this research partially show that the age variable (X1) has a significant effect on work productivity. The length of service variable (X2) has a significant effect on labor productivity (Y).